IKHWAN AL-MUSLIMIN DAN PERJUANGAN MENEGAKKAN PEMERINTAHAN ISLAM DI MESIR, 1948-1954 (Ikhwan al-Muslimin and the Struggle in Establishing the Islamic Goverment in Egypt, 1948-1954) - Othman, Mohammad Redzuan; Haris, Abu Hanifah (Journal of Al-Tamaddun, 2018)
This study discusses the struggle of the al-Ikhwan al-Muslimin in establishing the Islamic government in Egypt from 1948 to 1954. This period was considered important in Egypt's political history because 1948 marked the establishment of the Israeli state in Palestine and Egypt was forced to fight with Israel for the first time. In 1954, al-Ikhwan al-Muslimin was banned and many of its members were arrested and sentenced. This study uses qualitative approach and library study method to analyze various primary and secondary sources. The findings of this study reveal that the death of Hasan al-Banna in 1949 was a turning point that changed the journey of the movement because Hasan al-Banna’s succeeding leader was unable to compete with the former’s leadership and personality. Hasan al-Banna’s death was also a major factor in the failure of the movement. Although al-Ikhwan al-Muslimin is the most influential organization in the Middle East, the movement has not succeeded in mastering the politics of Egypt and Arab countries. Moreover, the movement was defeated by Free Officers with smaller members. Al-Ikhwan al-Muslimin has also made some failed political calculations, including the credentials given to General Mohamed Neguib who eventually led the ban on the movement. Many members were then arrested by Gamal Abdel Nasser in 1954 for conspiring with Neguib.